286. Computed Tomography profile analysis with radiochromic films. (December 2018) - Spampinato, S.; Gueli, A.; Raffaele, L.
Abstract : Purpose: This work proposes the use of radiochromic film dosimetry for Multi-Slice Computed Tomography (MSCT) profile analysis along the scanner detector array. For this purpose, Gafchromic® XR-QA2 films were used for single and multiple scans in axial and helical modalities with a MSCT scanner. Methods: Radiochromic films were cut into long strips and were irradiated with a MSCT scanner on an air-equivalent block. After irradiation, films were digitized with a commercial flatbed scanner using a resolution of 72 dpi, a colour depth of 48bit and saved in TIFF format. Images were calibrated in kerma in air and profiles were then extracted to obtain information on several parameters. The single scan profile analysis, carried out by maintaining stationary the MSCT couch, allowed to obtain the Radiation Profile Widths (RPWs), overbeaming values and detectors geometric efficiency for different beam collimations (range 1.25–40 mm). The multiple scans profile analysis was carried out for both axial and helical acquisitions, keeping the scan length constant for the different collimations used (20–40 mm). This provided information on the overranging parameter for helical acquisitions and the overbeaming effect in multiple scans. Results: The single analysis has allowed to verify that the RPWs measured values coincide with those declared by the manufacturer, as shown in Table 1. In addition, it was possible to verify the extent of the overbeam according to the beam collimation. Finally, it was possible to calculate the geometric efficiency of the detectors as a function of the beam collimation. The multiple scans profile analysis showed that overbeaming effect leads to an overall dose increase in axial CT acquisitions. Regarding the helical modality, the analysis has shown that overranging values depend on the collimation and increases for larger collimations. Conclusions: Radiochromic films are suitable for CT applications and allow to obtain information concerning MSCT profiles for single and multiple profile scans and for axial and helical modalities with high spatial resolution.